Bills limiting or increasing the legal protection of life in Poland after 1997 - Baran, Bartłomiej; Melon, Jan (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter describes attempts to change Poland's abortion law from 1994 to 2020, covering all citizens' and deputies' bills aimed at expanding access to abortion, except the 2006 bill to amend the Constitution, alongside all bills aimed at more effectively protecting the lives of children at the prenatal stage.The analysis shows that most attempts to undermine the so-called abortion compromise have come from left-wing groups seeking to lower Poland's standard of protection for human life by introducing a "right to abortion," or at least shaping its preconditions so that abortion within the first twelve weeks of conception would be unrestricted. These bills disregarded fathers' rights entirely, treating the decision to end a child's prenatal life as the mother's sovereign act of will.Allegations that conservative circles are exclusively responsible for pursuing a "violation of the abortion compromise" are therefore unjustified.